Carpal tunnel syndrome following an electrical injury in a child. (2nd March 2015) - Anand, Sambandam; Findlay, Alice Rima; Anand, Geetha
Abstract : Carpal tunnel syndrome (CTS) is very rare in children and has been reported very infrequently in the literature. We present an unusual case of CTS in a 14-year-old girl who developed this following an accidental electrical shock. As far as we are aware, this is the first case report of CTS in a child following electrical injury. This rare complication of electrical injury can easily be disregarded or misdiagnosed as neuropraxia, and this can delay appropriate treatment, as evidenced by this case. We propose that CTS should be considered when instigating initial medical care after an electrical injury, and that a referral to a hand surgeon should not be delayed, as these children need urgent surgical intervention to preserve hand function.